Age-related differences in bimanual coordination performance. Issue 2 (3rd April 2021) - Roman-Liu, Danuta; Tokarski, Tomasz
Abstract : Purpose . The purpose of this article was to determine how characteristics of bimanual coordination tasks affect the quality of performance and to determine the impact of these characteristics on muscular activation of the upper limbs, with consideration of age-related differences. Methods . The research was carried out on two groups consisting of 25 people aged 20–30 and 60–67 years. The subjects performed seven tasks that varied in coordination mode, tracking mode and outline-tracing. The main measures of task performance were calculated on the basis of the difference between the position of the target and tracing cursors. Cohen's d value was calculated to show differences in measures between groups. Results . There were higher values of error and variability measures for elderly people compared to young. Complex tasks showed the largest difficulty, which suggests that, when performed, such tasks have the greatest potential to improve coordination skills. Tasks during which both limbs contribute to the movement of one cursor proved the most appropriate. Conclusion . The tracking mode is of great importance for the quality of performance in motor coordination tasks, while the performance of tasks with imposed speed is much more strongly age-sensitive than performance with a freely chosen speed.